Implementation and sustainability of mentorship for public health student success - Grilo, Stephanie A.; Joseph, Michael A.; Samari, Goleen (Frontiers in Public Health, 2025)
Historically underrepresented and marginalized (URM) graduate students in public health, including students of color, first-generation, and international students, often face structural inequities such as limited representation among faculty, insufficient professional networks, and lack of structured mentorship. In response, the Mentoring of Students and Igniting Community (MOSAIC) program was established in 2019 at Columbia University’s Mailman School of Public Health. MOSAIC aims to provide structured, equity-centered mentorship designed to enhance academic success, professional development, and community-building for URM students. This manuscript outlines the implementation and evolution of MOSAIC over 5 years, highlighting key processes in its design, preparation, implementation, and sustainability. The program uniquely integrates anti-racist and anti-oppressive pedagogical frameworks, prioritizes student-driven programming, and involves committed, compensated faculty mentors from diverse backgrounds. Initial evaluations demonstrate positive outcomes, including improved student satisfaction, sense of belonging, and overall quality of life. The sustainability of MOSAIC was achieved through strategic actions such as securing institutional funding, fostering administrative buy-in, recruiting faculty champions, and collaborating with existing campus resources. MOSAIC’s substantial growth from 26 participants in its inaugural year to over 450 by 2024 underscores its effectiveness and the broader institutional commitment to inclusive excellence. This paper uses the implementation and sustainability of MOSAIC at Columbia Mailman to show other public health institutions aiming to replicate and sustain mentorship programs how they can support URM students but also foster institutional transformation toward equity and inclusion.